The allele frequency of CYP2C9 and VKORC1 in the Southern Khorasan population - Razavi, Fariba Emadian (Res Pharm Sci, 2017)
The genetic factors are determinants in required dosage changes of warfarin among which are polymorphisms of CYP2C9 and VKORC1 genes. The present study aimed to determine the allele and genotype frequency of CYP2C9 and VKORC1 genes in Birjand population. This study was conducted on 120 individuals who referred to Imam Reza and Vali-Asr hospitals for PT/INR test. After extracting the genomic DNA, the considered sequences were amplified by PCR, and restriction fragment length polymorphism analysis was done by AvaII and KpnI enzymes to determine allele polymorphisms. Moreover, related sequences of VKORC1, after amplification, were sequenced for determining the genotype. Allelic and genotypic frequencies as well as Hardy-Weinberg equilibrium, observed heterozygosity, expected heterozygosity, and polymorphism information content were calculated by PowerMarker V 3.25 software. Amongst 120 individuals in this study with the mean age of 58.12 ± 12.7 years, 80.8%, 9.1%, and 10% exhibited the alleles of 1, 2, and 3 CYP2C9 gene, respectively. The genotype frequencies of 1/1, 1/2, 2/2, 3/1, 3/2, and 3/3 of this gene were found to be 64.1, 15.8, 0, 17.5, 2.5, and 0 %, respectively. In -1639 G>A region, VKORC1 had normal homozygote genotype (GG) and in 1173 C>T region, heterozygote (CT) with the frequency of 48.7% and 45.9% had the most prevalence. Compared with other populations, there is a considerable difference between the allele frequency of CYP2C9 and VKORC1 genetic variance. Since 35.8% of the selected populations carry an abnormal allele causing sensitivity to warfarin, the specialists at medical centers must be informed about the genotypes of patients before prescribing warfarin.